An analytical cross sectional study on hypothyroidism in pregnancy, its maternal and fetal outcome - S., Vinodhini; S., Vilvapriya; K., Veeraragavan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypothyroidism is associated with maternal and fetal complications. This study aims to evaluate the prevalence, maternal and fetal outcome in hypothyroidism. Objective of this study was to determine whether thyroid function test can be recommended as a universal or selective screening in pregnancy. Methods: An analytical cross-sectional study with internal comparison carried out at Govt. Kilpauk Medical College & Hospital from September 2017 to July 2018 for antenatal mothers in third trimester. Serum TSH and freeT3, T4 in case of abnormal TSH were measured, grouped into subclinical and overt hypothyroidism and were treated with Levothyroxine. Six-week follow-up with TSH, pregnancy complications were observed. Results: 932 pregnant mothers were followed up. Prevalence of hypothyroidism was 10.5% (n = 98). Among the hypothyroid 62.24% (n = 61) had subclinical and 37.76% (n = 37) had overt hypothyroidism. The prevalence of anaemia was 35% in overt and 15% in subclinical hypothyroid group (p = 0.019). Preeclampsia is reported in 49% of overt and 16% of subclinical hypothyroid group (p = <0.001), statistically significant. Eclampsia was noted in 1 (1.64%) overt hypothyroid patient. Abruptio placenta was observed in 1 subclinical and 4 overt hypothyroid patients (5.1%). The incidence of preterm labour in this study subjects was 38% in overt and 20% in subclinical hypothyroid group (p = 0.048). The incidence of LBW fetus was 41% in overt hypothyroid and 21% in subclinical hypothyroid group (p = 0.041). The incidence of complication in this study was 41% in subclinical and 78% in overt hypothyroid group (p = <0.001). Conclusions: Early screening, adequate treatment and follow up will bring down maternal and fetal complications in hypothyroidism.